Der Institutionalisierungsprozess des Lohnarbeitsverhältnisses vom Ersten bis zum Zweiten Weltkrieg in Deutschland - Michael J. Kendzia (Institute for the Study of Labor (IZA), 2010)
– The paper provides a historical overview of the institutional development of the structural elements of the standard employment contract in Germany from the beginning of World War I until the outbreak of World War II. For this purpose, a model of the standard employment contract including certain structural elements is used, which represents the standard employment contract in the early 1970s. The analysis deals with the determining factors of the emergence and adjustment of these elements and traces back the intentions of each actor involved. The focal point is the legal arrangement of employment contracts between employees and employers. The historical perspective shows that the legal structure of the working relationship depends on the particular social and political balance of power of the time. The relation between the position of each interest group within society and its implications is especially observed during periods of severe political disruption.
Keywords: J50; J40; 330; Lohnarbeitsverhältnis; Normalarbeitsverhältnis; Weimarer Republik; Hilfsdienstgesetz; Arbeitslosenversicherung; Ruhreisenstreit; Arbeitsvertrag; Arbeitsverhältnis; Institutionalismus; Geschichte; Deutschland (bis 1945)